Pengabdian kepada Masyarakat: Pelatihan Keperawatan Komunitas untuk Kader Kesehatan dalam Meningkatkan Kesehatan Masyarakat di Wilayah Desa Tapalang Kab. Mamuju Sulbar Tahun 2024 - Musdalifah, Musdalifah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Community service is one way to implement the knowledge and skills possessed by health workers to improve the quality of life of the community. Tapalang Village, Mamuju Regency, West Sulawesi, is an area facing challenges in accessing health services, particularly in promotive and preventive efforts. Therefore, community nursing training for health cadres is crucial to enhance their role as spearheads in public health services. The objective of this activity is to improve the knowledge, skills, and attitudes of health cadres in early detection of health problems, providing education, and supporting the establishment of clean and healthy living behaviors (PHBS) in the community. Implementation methods include lectures, discussions, simulation practices, and direct mentoring. The results of the activity show a significant increase in health cadre knowledge from 58% before training to 87% after training, as well as improved skills in providing health education. This activity is expected to strengthen the role of cadres in supporting government health programs at the village level.